The Basic Helix-Loop-Helix Transcription Factor SmbHLH1 Represses Anthocyanin Biosynthesis in Eggplant - Duan, Zhaofei; Tian, Shiyu; Yang, Guobin; Wei, Min; Li, Jing; Yang, Fengjuan (Frontiers in Plant Science, 2021)
Many basic helix-loop-helix transcription factors (TFs) have been reported to promote anthocyanin biosynthesis in numerous plant species, but little is known about bHLH TFs that inhibit anthocyanin accumulation. In this study, SmbHLH1 from Solanum melongena L. was identified as a negative regulator of anthocyanin biosynthesis. However, SmbHLH1 showed high identity with SmTT8, which acts as an SmMYB113-dependent positive regulator of anthocyanin-biosynthesis in plants. Overexpression of SmbHLH1 in eggplant caused a dramatic decrease in anthocyanin accumulation. Only the amino acid sequences at the N and C termini of SmbHLH1 differed from the SmTT8 sequence. Expression analysis revealed that the expression pattern of SmbHLH1 was opposite to that of anthocyanin accumulation. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays showed that SmbHLH1 could not interact with SmMYB113. Dual-luciferase assay demonstrated that SmbHLH1 directly repressed the expression of SmDFR and SmANS. Our results demonstrate that the biological function of bHLHs in anthocyanin biosynthesis may have evolved and provide new insight into the molecular functions of orthologous genes from different plant species.